Synthesis and analysis of new non-corrosive hot aerosol fire suppression agent - Zhang, Xiaotian; Ismail, Mohd Halim Shah; Ahmadun, Fakhrul-Razi; Abdullah, Norhafizah (IDOSI Publications, 2014)
A synthesized new S-type aerosol forming agent composed of strontium nitrate and magnesium powders majorly is developed to replace currently dominate corrosive K-type aerosol forming agent which is based on potassium nitrate on the market. In fire extinguishing test, new S-type aerosol forming agent can effectively kill a heptane fire in less than 20s in a 1 m compartment and the surface resistivity of the new S-type 3 aerosol precipitates on a PVC membrane is 10 ±0 which is very effective for anti-corrosion. Further corrosion 11 test shows that new S-type aerosol brings much less damages to copper plate than traditional K-type aerosol. After oxidation-reduction process of aerosol forming agent, percentage of strontium compounds both in aerosols and residues were analyzed by EDX. And through heat balance modeling, time evolution of nozzle temperature of the canister containing aerosol forming agent was predicted and compared with experimental data and the prediction can fit the experimental data well. Though the nozzle temperature is very high during aerosol generating, such problem can be solved by developing aerosol forming agent coolant in the future.